Implementation of Context-Environment Design: Ecocentric Study in Bus Stops - Luna Rodríguez, Sofía (UNIVERSIDAD DE SONORA, 2021)
Nowadays, anthropocentric design theories explain that the empathic and user-centered side has been a fundamental part in the creation of products, services, and systems over the years, however, the results do not manage to be sufficiently competent to consider external factors to the user such as natural environments, contexts external to the human, trends, and relationships to futurology. This is why implementing broader approaches and considering valuable aspects such as biology, sociology, the study of trends, anthropology, and the environment, together with the human-empathic factor, a complete design result can be achieved. This project was born from the concern to apply new approaches to design methods for the creation of products, spaces, and systems that coexist in the daily life of the human being, through a methodology based on the context-environment called "Generation of oriented ideas to ecosystems”, in this case, for a bus stop in the City of Monterrey, Nuevo León, Mexico. The selected design concept presents the relevant characteristics defined from the generation of ideas oriented to ecosystems and complying with the State Technical Standard for Sidewalks of Nuevo León, allowing a complete design based on the objectives of the context to which it is directed.